Conceptual Studies on Cellular Aging and Programmed Cell Death in Light of Swabhavoparama Vada and Kshanabhangura Vada - Majumder , Bijita; Ray , Sukalyan (International Research Journal of Ayurveda & Yoga, 2022)
In this universe, no living being is eternal. Birth and death are the two terminal point of life. Where we can point out to many causes of genesis, there is no absolute reason behind the annihilation of beings as it becomes certain once a creature is born , it will going to die one day. Every biological cycle has its own causes for its start-up but it has come to end one moment with no absolute cause behind for its cessation. Cells are the structural and functional unit of every living beings. Cells normally maintain a steady state called homeostasis in which the intracellular milieu is kept within a fairly narrow range of physiologic parameters. But every cell under goes aging and ultimately death. Cell death is one of the most crucial events in the evolution of disease in any tissue or organ. Cell death also is a normal and essential process in embryogenesis, the development of organs, and the maintenance of homeostasis. A number of cellular functions decline progressively with age. Cellular aging is the result of a progressive decline in the life span and functional capacity of cells. Although many theories have been propounded why the cell attains senescence and death, we still actually don’t know why these senescence and death cannot be avoided and these become certain for every cell. In absence of proper explanation, the need of the hour is to study both the phenomenon i.e. cellular aging and apoptosis in comparison with the Ayurvedic doctrine of Swabhavoparama Vada (doctrine of natural destruction) and Buddhist doctrine of Kshanabhangura Vada (doctrine of momentariness). The proper understanding of these eternal theories may help us to find answers of many unsolved questions regarding cell’s life cycle and can open the doors of possibilities for new research and discoveries.